염화칼슘이 함침된 펄라이트를 이용한 화학축열에 대한 실험적 연구 - 정한솔(Han Sol Jung); 김학성(Hak Seong Kim); 황경엽(Kyung Yub Hwang); 김광호(Kwang Ho Kim) (설비공학 논문집, 27(3), 2015)
Thermochemical heat storage is a cutting-edge technology which can balance the energy usage between supplies and demands. Recent studies have suggested that thermochemical heat storage has significant advantages, compared to other storage methods such as latent heat storage or sensible heat storage. Nevertheless, ongoing research and development studies showed that the thermochemical heat storage has some serious problems. To bring the thermochemical heat storage method into market, we introduce experimental setup with composite material using perlite that supports calcium chloride sorbent. Also, to compare thermal properties with composite material, we used pure thermochemical material. Then, we found that the composite material has higher heat storage density by mass than pure calcium chloride. Moreover, it can be easily regenerated, which was impossible in the pure thermochemical materials.